Impact of Accounting Information System and Intensity of Energy on Energy Consumption in Sugar Industry of Indonesia: Moderating Role of Effectiveness of Supply - Meiryani, Meiryani; Suzan, Leny; Sudrajat, Jajat; Joemsittiprasert, Watcharin (International Journal of Energy Economics and Policy, 2020)
The goal of the existing study is to explore the impact of accounting information system (AIS) and intensity of energy on the effective energy consumption of the sugar industry in Indonesia. The goal also consist upon the moderating role of effectiveness of supply chain on the links of AIS and effective energy consumption, intensity of energy and effective energy consumption. The employees that are related with AIS and supply chain are the respondent and they provide the data by questionnaires and the data was evaluated by employing the effective tool of data analysis named as Smart-PLS. The results show that AIS and intensity of energy have positive link with the effective energy consumption. The findings also show that effectiveness of supply chain positively moderates among the links of AIS and effective energy consumption, intensity of energy and effective energy consumption. The policymakers and the upcoming researchers will be the users of this study who can get guidelines in developing regulation regarding effective energy consumption and also in exploration of this area in future. Keywords: Intensity of Energy, Effective Energy Consumption, Accounting Information System, Supply Chain JEL Classifications: O13, E16 DOI: https://doi.org/10.32479/ijeep.10221